Shifting Work Paradigms: Legal Perspectives on India’s Digital Revolution - Paramita Bhattacharyya; Sudipta Adhikary (New Advances in Business, Management and Economics Vol. 1, 2025)
The rapid advancement of technology has been accompanied by a digital revolution that is redefining work dynamics across the globe, with India at the forefront of this transformation. The explosion of digital platforms, remote work models, and gig economy structures has given rise to new challenges and opportunities for both employers and employees. This paper explores the shifting paradigms of work in India, focusing on the legal frameworks that govern this evolving landscape. India’s labor laws, traditionally designed to address conventional employment models, are undergoing a significant transformation to adapt to the demands of the digital economy. The paper focuses on the regulation of gig and platform workers under the Code on Social Security, 2020. The rapid advancement of digital technology has profoundly affected individuals’ right to privacy. This ongoing evolution of privacy legislation underscores the complex interplay between data collection, technological innovation, and individual rights. By exploring the historical development of privacy regulations, their roots in traditional legal systems to their modern application in the digital era have been traced. The study also examines the legislative efforts to bridge the gap between technological advancements and the protection of workers’ rights, emphasizing the need for inclusive and flexible policies. By providing insights into the intersection of technology, work, and law, this paper aims to contribute to the discourse on creating a balanced regulatory framework that supports economic growth while safeguarding the rights and dignity of the Indian workforce in the digital age. The paper further explores how companies in India connect workers with tasks through online platforms. These platforms use algorithms to assign piece-rate jobs to independent partners/contractors. One of the key challenges in this area is the reliance on algorithms to assign piece-rate jobs to independent partners or contractors. While this approach enables efficiency and scalability, it raises concerns about fairness, transparency, and accountability in the allocation process. Additionally, the rapid expansion of the digital economy, particularly after the COVID-19 pandemic, has intensified the role of the platform economy, further complicating issues such as worker classification, rights, and equitable treatment.